Solute induced phase separation and droplet encapsulation - Wang, Ruoxu (2019)
The scope of this research is to expand the design of nano-synthesis from solid particles to liquid droplets. In the research area of nano-synthesis, a variety of strategies have been developed based on the understanding of fundamental principles of solid nucleation and growth. We aimed on following this example to lay the foundation of droplet nano-synthesis (Chapter 1). Solid nano-synthesis starts from building solid materials bottom-up from a liquid phase. Top-down method such as grinding down solid chunks would hardly yield complicated nano-structures in a controllable manner. However, traditional method of producing small droplets is through breaking continuous liquid phase down, which is considered as top-down. Therefore, it would be crucial to develop a bottom-up method of building liquid materials so that the way towards droplet nano-synthesis can be paved. Solute induced phase separation is the key. The most common one among this kind of phenomena is salting out, which represents the phase separation of two previously miscible solvents induced by the addition of salt. By controlling the release of salt in a water-ethanol mixture, uniformed droplets with a narrow size distribution have been synthesized. Silica nano-encapsulation and thickeners were introduced to capture these droplets for characterizations (Chapter 2). The generality of salts has also been verified based on the Hofmeister series. Inspired by the kosmotrope-chaotrope theory, the choice of solute has been further generalized to a series of kosmotropes other than salts. A variety of substances can be loaded into droplets synthesized through the phase separation process. Therefore, nano-encapsulation of those substances has been achieved through capturing the loaded droplets (Chapter 3). There are three routes of loading, pre-, peri-, and post loading. In pre-loading, the loaded substance itself induces the phase separation. Peri-loading indicates the loading during the formation and growth of droplets. Post-loading happens after the formation of droplets. Following these routes, Au(III), Ag(I), Cu(II), Pt(IV), Pd(II) complex salts, cisplatin and doxorubicin have been loaded into silica nano-capsules. The advantages and shortcoming of the three routes have also been analyzed. Other materials have been applied to the nano-encapsulation of droplets (Chapter 4). Nano-capsules made from polydopamine, resorcinol formaldehyde resin, copper-trimesic acid metal organic framework, iron oxide, other metal oxide and insoluble salts have been synthesized. Also, a series of polydopamine-silica hybrid capsules were applied in the nano-encapsulation of droplets generated from phase separation. By manipulating the droplet growth, a double layer structure with a gap between both layers has been synthesized through a one-pot reaction. The fluidity of droplet could also lead to complicated asymmetric nano- structures. Based on a work in a literature, water post-loading was applied to synthesize nano-bottles with multiple bellies and dumbbell-like hollow structures (Chapter 5). The mechanism of their formation has been further analyzed and elaborated. Finally, based on the data above and the result of a series of new experiments, two droplet nucleation hypotheses in the solute induced phase separation system have been raised (Chapter 6). The liquid particle hypothesis is a proximation modified from solid particle nucleation and growth. The condensation and extraction hypothesis is inspired from the polygonal-shaped capsules observed under certain reaction conditions. After a thorough analysis and reasoning, the latter hypothesis has been improved to explain two trends observed in experiments.